Improving English Vocabulary Mastery Through The Memrise Application for Twelve Grade Students MA Al Djufri: A Classroom Action Research - Hasanah, Yusrotul; Sumo, Maimon; Maufiroh, Faikotul; Listyowati, Rini; Ruaida, Siti (IKIP Siliwangi, 2025)
The aims of this research is to find out how students perceive and understand the memrise application as a tool to learn and improve the understanding of English vocabulary. Classroom Action Research (CAR) is the method of this research. The subjects in this research are twelve grade students with a total of 30 students at MA Al Djufri Pamekasan. The time of this research is from the month of October to November 2024. In this research, the author used observation sheet and test instruments. The results of this research in cycle 1 were 64.4 while the results of this research in cycle 2 were 93. Results In cycle 1, these results were supported by the results of observation of teacher activities by achieving an average of 87% and student observation results of 74.8%, while the results in cycle 2 were supported by the results of observation of teacher activities by achieving an average of 94% of enthusiasm and 89.6% of student implementation observations. Students' vocabulary knowledge and learning engagement can be enhanced by utilizing the memrise application.